The Effect of The Student Facilitator and Explaining Cooperative Learning Model on The Mathematical Problem-Solving Ability of Grade IX Students at Junior High School Tiga Hati Kepenuhan Hulu - Purba, Rika Wulandari Br; Arcat, Arcat; Afri, Lusi Eka (Jurnal Biochamp, 2025)
This study aims to determine the effect of the cooperative learning model, Student Facilitator and Explaining, on students' mathematical problem-solving abilities in Grade IX of SMP Tiga Hati Kepenuhan Hulu. The research employed a quantitative approach with a quasi-experimental design. The study subjects were Grade IX students divided into two groups: the experimental group, which was taught using the Student Facilitator and Explaining model, and the control group, which was trained using a conventional learning model. Data were collected through a mathematical problem-solving ability test. The hypothesis testing results showed that the t-value (2.37) was greater than the t-table value (2.12) at a significance level of α = 0.05. Therefore, H₀ was rejected and H₁ was accepted. This indicates a significant effect of the Student Facilitator and Explaining cooperative learning model on students’ mathematical problem-solving abilities